Attachment–aversion (AA) model of customer–brand relationships - Park, C. Whan; Eisingerich, Andreas B.; Park, Jason Whan (Journal of Consumer Psychology, 2013)
AbstractThe present paper proposes a customer–brand relationships model and empirically tests the following: (1) brand–self distance and brand prominence as representing customers' attachment–aversion relationships (AA Relationships) with a brand, (2) key distinguishing differences between the AA Relationships measure and other alternative relationship measures (i.e., brand attachment, emotional valence and brand attitude strength) based on a set of dependent variables, (3) three key determinants of the AA Relationships and the underlying process between the AA Relationships and behavioral intentions and actual brand behaviors, and (4) customer age as moderating the customer–brand relationships specified in the nomological model of the AA Relationships. The results offer strong support for the unique and important contribution of the AA Relationships model as representing consumers' relationship valence with a brand and its salience.